True believer [compact disc, unabridged] - Sparks, Nicholas (Books on Tape, 2005)
As a science journalist with a regular column in Scientific American, Jeremy Marsh specializes in debunking the supernatural and has a real nose for the strange and unusual. A born skeptic, he travels to the small town of Boone Creek, North Carolina, determined to find the real cause behind the ghostly apparitions that appear in the town cemetery. What he doesn't plan on, however, is meeting and falling hopelessly in love with Lexie Darnell, granddaughter of the town psychic. Now, if the young lovers are to have any kind of future at all, Jeremy must make a difficult choice: return to the life he knows, or do something he could never do before-take a giant leap of faith.